Comparison between BS 8110: Part 1: 1997 and Eurocode 2 for design the reinforced concrete slab - Masri Hana Mohd Apandi (School of Environmental Engineering, University Malaysia Perlis, 2013)
In this study, the objective of research is to compare the difference in the concept of the design using BS 8110: Part 1 : 1997 and EC 2, to compare manual calculation and spreadsheet of Microsoft Excel 2007 for 3 types of slabs and to prepare a spreadsheet for the analysis and design of slabs.